Airborne Bacterial Interactions: Functions Out of Thin Air? - Audrain, Bianca; Létoffé, Sylvie; Ghigo, Jean-Marc (Frontiers in Microbiology, 2015)
Bacteria produce and release a large diversity of small molecules including organic and inorganic volatile compounds, hereafter referred to as BVCs. Whereas BVCs were often only considered as wasted metabolic by-product sometimes perceived by animal olfactory systems, it is increasingly clear that they can also mediate cross-kingdom interactions with fungi, plants and animals. Recently, in vitro studies also reported the impact of BVCs on bacterial biology through modulation of antibiotic resistance, biofilm formation and virulence. Here, we review BVCs influence on bacterial adaptation to their environment and discuss the biological relevance of recently reported inter- and intra-species bacterial interactions mediated by BVCs.